An Exploratory Retrospective Study of Factors Affecting Energy Expenditure in Critically Ill Children. Issue 3 (2nd July 2019) - Mtaweh, Haifa; Garros, Christiana; Ashkin, Allison; Tuira, Lori; Allard, Johane P.; Pencharz, Paul; Pullenayegum, Eleanor; Joffe, Ari; Parshuram, Christopher S.
Abstract: Background: Accurate measurement of energy expenditure is not widely available. Patient and clinical factors associated with energy expenditure have been poorly explored, leading to errors in estimation formulae. The objective of this study was to determine clinical factors associated with measured energy expenditure (MEE), expressed in kcal/kg/d, in critically ill children. Methods: This was a retrospective study at 2 Canadian pediatric intensive care units (ICUs). Patients were mechanically ventilated children who had 1 or more MEE using indirect calorimetry. Associations between MEE and 28 clinical factors were evaluated in univariate regression and 16 factors in a multivariate regression model accounting for repeated measurements. Results: Data from 239 patients (279 measurements) were analyzed. Median (Q1, Q3) MEE was 34.8 (26.8, 46.2) kcal/kg/d. MEE was significantly associated with weight, heart rate, diastolic blood pressure, ICU day of indirect calorimetry ( P = 0.004), minute ventilation, vasoactive inotropic score ( P = 0.004), opioids, chloral hydrate, dexmedetomidine, inhaled salbutamol ( P = 0.02), and propofol dose (all P < 0.0001 unless otherwise specified) in the final multivariate regression model. Conclusions: This study demonstrated association between MEE (kcal/kg/d) and factors not previously explored in pediatric critical illness. Further evaluation of these factors to confirm associations and more precisely quantify the magnitude of effect is required to support refinement of formulae to estimate energy expenditure.